Wealth and Homeownership Women, Men and Families - Rossi, Mariacristina (Springer International Publishing, 2018)
'Recently, economists studying wellbeing have widened their lenses beyond income to include wealth. Here, economists Rossi and Sierminska tap new high-quality datasets to assess how wealth and homeownership vary across countries, over time, and among household types. Economists and policy-makers interested in wealth will find much of interest in this book.' -Janet C. Gornick, City University of New York, USA 'This book attacks crucial issues, presenting well-documented facts and rigid analysis. It reveals time-trends and cross-national differences and explains the decisive role of wealth accumulation over lifetimes.' -Klaus F. Zimmermann, Maastricht University, the Netherlands In almost every country, wealth is predominantly constituted by housing equity, but what are the possible risks and how does wealth accumulation vary across countries? In this timely book, Rossi and Sierminska analyse the complex relationship between gender, wealth and homeownership. By providing a conceptual framework to insert homeownership and housing decisions within an economic rationale, the authors explore how gender and family types have shaped wealth accumulation and homeownership. Mariacristina Rossi is Associate Professor of Economics at the University of Turin, Italy and Senior Researcher at CeRP-CCA, Italy. Her research interests include intertemporal saving and consumption choices, household finance, development and gender economics. Eva M. Sierminska is Senior Researcher at the Luxembourg Institute of Socio-Economic Research, Luxembourg and Research Fellow at IZA, Germany, DIW Berlin, Germany and GLO, Germany. She is a labor economist and has extensive research experience in the area of labor markets, inequality, household finance and population economics. .